THE REPRESENTATION OF GENDER IDEOLOGY IN THE EARLY CHILDHOOD EDUCATION TEACHER’S HANDBOOK - Laksono, Kisyani; Anistyasari, Yeni; Nasrullah, Riki; Imawati, Endah (Veredas do Direito, 2026)
Books that are regularly read shape readers' thinking and views. This study aims to critique and uncover how gender ideology is constructed in The Early Childhood Education Teacher's Handbook (ECETH) by (1) identifying gender ideology as a societal discourse; (2) explain-ing ideological co-existence in the form of naturalisation and gender resistance; and (3) for-mulating asymmetric gender progressivism. This study adopted a mixed-methods approach, supported by qualitative descriptive methods. Data were obtained from six books and a com-pleted questionnaire. Data analysis was conducted using critical discourse analysis and NVi-vo. The results show that gender ideology is not a stable or fixed worldview but rather a dis-cursive formation shaped by social contingencies that depend on professional, locally embed-ded institutional structures, policies, and practices. Gender is naturalized in terms that do not constitute an explicit challenge to gender equality, but rather an implicit refinement process that maintains existing hierarchies while allowing some room for modification. Asymmetric gender progressivism helps explain why gender-inclusive language and imagery coexist with largely intact inequality. This is a crucial realization in the debate about changing gender norms and in the endeavor to develop genuinely inclusive pedagogical resources.